2009
DOI: 10.4049/jimmunol.0903071
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Mast Cell Synapse: FcεRI Membrane Dynamics upon Binding Mobile or Immobilized Ligands on Surfaces

Abstract: High affinity IgE receptors (FcεRI) on mast cells form a “synapse” when presented with mobile, bilayer incorporated antigen. Here, we show that receptor reorganization within the contacting mast cell membrane is markedly different upon binding of mobile and immobilized ligands. Rat basophilic leukemia mast cells (RBL-2H3) primed with fluorescent anti-DNP IgE were engaged by surfaces presenting either bilayer-incorporated, monovalent DNP-lipid (mobile ligand) or chemically crosslinked, multivalent DNP (immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
87
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 77 publications
7
87
0
Order By: Relevance
“…Our data extend data reported by Wu et al who focused on localized endosomal recycling and not on mast cell degranulation 30 . In agreement with this and other reports [30][31][32] , we show that FcR and the associated signalling component LAT cluster in the proximity of the budding granules. These results, together with the observation of a localized clearance of actin cytoskeleton at the degranulatory synapse, provide a mechanistic link between localized signalling and polarized secretion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data extend data reported by Wu et al who focused on localized endosomal recycling and not on mast cell degranulation 30 . In agreement with this and other reports [30][31][32] , we show that FcR and the associated signalling component LAT cluster in the proximity of the budding granules. These results, together with the observation of a localized clearance of actin cytoskeleton at the degranulatory synapse, provide a mechanistic link between localized signalling and polarized secretion.…”
Section: Discussionsupporting
confidence: 93%
“…Silverman et al showed that FceRI and the associated signalling components such as SLP76, Syk and LAT selectively cluster at the site of stimulation 31 . Carroll-Portillo et al showed that FcR clusters are detectable at the mast cell/lipid bilayer contact area 1 min after stimulation and then, they coalesce leading to the formation of a mast cell synapse 32 . Using patterned lipid bilayers, Wu et al reported that secretion is directed towards the substrate where the stimuli are located, but do not strictly co-localize with the signalling clusters 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flat sheets of plasma membranes from the apical cellular surface were prepared from virus-infected or transfected cells and processed for electron microscopy by a variation of the "membrane rip" technique (49,50). This type of analysis has been used successfully to examine the membrane distribution of a single protein, such as the IgE receptor FcR1 and CC chemokine receptor 5 (51)(52)(53). These analyses has also been extended to compare two protein populations to each other, showing whether or not they specifically cocluster with each other, for example, prion protein, AP2, transferrin receptor (54), FcR1, tyrosine kinase Lyn (55), lipid raft markers (56), Ras proteins (57), and a preliminary examination of influenza virus M1, M2, and HA (58).…”
mentioning
confidence: 99%
“…Studies include effects of D 2 O on tobacco seed growth (Lewis, 1934), IgE-Mediated histamine release from human leukocytes (Gillespie and Lichtenstein, 1972), actin filament velocities (Chaen et al, 2001), protein flexibility (Cioni and Strambini, 2002), human pancreatic tumor cells (Hartmann et al, 2005), phospholipid membranes (Beranova et al, 2012), kinesin-1 gliding assay (Maloney et al, 2014), and stabilization of tubulin as observed previously in microtubule gliding assays (Panda et al, 2000) and in biochemical experiments on isolated tubulin proteins from beef brain (Houston et al, 1974) and goat brain (Das et al, 2008). Microtubules are polarized polymers of α/β tubulin heterodimers and undergo alternating phases of growth and shrinkage with sudden transitions between the two (Bartolini et al, 2005 In this paper we use the RBL-2H3 cell line, a typical mast cell model system (Thomas et al, 1992;Posner et al, 1995;Carroll-Portillo et al, 2010;Spendier et al, 2010), to start investigating this question. Mast cells are immune cells that originate from the bone marrow and circulate in an immature form in the body until they settle in tissue and mucosal surfaces, where they mature.…”
mentioning
confidence: 95%